The Suspended Middle : Henri de Lubac and the debate concerning the supernatural - Milbank, John. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2005)
"French Jesuit Henri de Lubac (1896-1991) was arguably the most revolutionary theologian of the twentieth century. He proposed that Western theology since the early modern period had lost sight of the key to integrating faith and reason - the truth that all human being are naturally oriented toward the supernatural." "In this vital book John Milbank defends de Lubac's claim and pushes it to a more radical extreme. The Suspended Middle shows how such a claim entails a 'nonontology' suspended between rational philosophy and revealed theology, interweaving the two while denying them any pure autonomy from each other."--BOOK JACKET.
1. The life and writings of Henri de Lubac -- 2. The 'Surnaturel' of 1946 -- 3. Around 'Humani generis' -- 4. Supernatural, spirit, and cosmos -- 5. The supernatural in relation to de Lubac's other theological thematics -- 6. De Lubac and von Balthasar contrasted -- 7. Thomistic criticisms of de Lubac on the supernatural : the aesthetic compromise -- 8. Aquinas and the radicalization of de Lubac's account of the supernatural -- 9. The limit and the renown of Henri de Lubac.
Includes bibliographical references and index.
Keywords: Lubac, Henri de, -- 1896-1991.; Supernatural (Theology) -- History of doctrines